Dibutyl Phthalate (DBP) Mediated Oxidative Stress, Cytotoxicity and Estradiol Synthesis in Cultured Ovine Granulosa Cell - Singh, Poonam K.; Nandi, Sumanta; Gupta, Paluru S.P.; Mondal , Sukanta (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Plasticizer Dibutyl phthalate (DBP), a potent reproductive toxicant, can cause damage to the granulosa cells, the key cells for the production of steroidogenic hormones. It may also affect other antioxidant enzymes for follicular development, affecting oocyte quality. The present study examined the DBP-induced oxidative stress and hormone synthesis from granulosa cells. Biochemical assays such as MTT (3- (-4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide ) for the study of cell viability, proliferation, and cytotoxicity, cupric reducing antioxidant capacity (CUPRAC) assay for the total antioxidant capacity, malondialdehyde (MDA) assay for the lipid peroxidation, and Enzyme-linked immunosorbent assay (ELISA) for estradiol synthesis were employed to evaluate the effect of DBP at a concentration of 0 (control), 1, 10, 25, 50, 100 µM for 5 days in cultured bovine granulosa cells. Our results revealed that DBP decreased cell viability, cell proliferation, induced oxidative cellular stress, and affected estradiol secretion in a non-dose-dependent manner. The lowest concentration of DBP (1 µM) had a significant decrease in cell viability and increased lipid peroxidation compared to those observed in the control groups. The total antioxidant enzyme (CUPRAC) activity was non significantly induced in all concentrations of DBP in treated granulosa cells. The estradiol synthesis was increased significantly as the DBP concentrations increased. This study suggested that DBP at a very low concentration affected the steroidogenic capacity, cell viability, and proliferation by altering the antioxidant enzyme activity and causing oxidative stress to the cell.